(untitled) (Multidisciplinary Journal of Science and Technology, 2023)
In this paper, the determination of lead ions in the waters of Surkhondarya was studied by the spectrophotometric method using Chromazurol S. The formation of a complex between lead and Chromazurol S in the ion exchange phase was studied. This formed phase allowed spectrophotometric determination of lead in drinking water. According to the obtained results, the detection sensitivity was 0.02 μg/ml, and this was proposed as one of the effective methods for determining lead in Surkhondarya waters.